THE IMPACT OF SOCIAL MEDIA ON THE PREVAILING CULTURE IN SOCIETY: A SOCIOLOGICAL STUDY - Dr. Khaled Nser, Dr. Rakan Alhrahsheh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper, the researchers analyze and explain the potential effects of social media on social culture. Therefore, the following main research question must be answered: How does social media affect an individual and society? The descriptive-analytical method was used as being the most suitable for such studies. The study tool was represented by a set of literature directly related to the subject of the study. The researchers will highlight the conditions of social media use in light of the prevailing culture. The examination is done at the global and individual levels; after that, the social media effects on the above two levels will be combined in one image. From the main results of this study, we can mention this: Social media has an effect on the emotions of individuals and the human brain and, consequently, on the quality of life, as emotions play a critical role in human communication, whereas social media has a significant benefit in communicating and transferring information. Whereas social media has a significant advantage in delivering and transferring data, and with that interest impacting the prevailing culture in society, it has an impact on customs and traditions. Culture remains the historical determinant of societies and individuals and is represented in their various behaviors, but the literature has shown that individuals can change traditional cultural patterns that do not fit with the requirements of the current era on the one hand, and on the other hand, they can cause the backwardness of society and the individual. The study recommends that more research be done in this aspect and that countries should focus on developing social policies in proportion to the cultural change that the world is witnessing and that they should open up to other cultures in all social areas.